117k views
4 votes
=Solve this system of equations byusing the elimination method.-X + 6y = 112x – 3y = 5([?],=

=Solve this system of equations byusing the elimination method.-X + 6y = 112x – 3y-example-1

1 Answer

4 votes

We have the following system of equations,


\begin{gathered} -x+6y=11 \\ 2x-3y=5 \end{gathered}

Using the elimination method.

Step #1. Multiply the 2nd equation by 2


\begin{gathered} -x+6y=11 \\ 4x-6y=10 \end{gathered}

Step #2. Eliminate +6y and -6y


\begin{gathered} -x=11 \\ 4x=10 \end{gathered}

Step#3. Add the values together


3x=21

Step#4. divide both sides by 3


x=(21)/(3)=7

So, we have x = 7

If x=7, then,


\begin{gathered} -7+6y=11 \\ 6y=11+7 \\ y=(18)/(6) \\ y=3 \end{gathered}

Thus, y=3

Answer: (7,3)

User Falcon User
by
6.2k points